KETERLIBATAN ORANG MUDA KATOLIK KEUSKUPAN KETAPANG DALAM KEGIATAN PASTORAL - Kristinus Sutrimo; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
The development and advancement of technology brings changes to the patterns and lifestyles of Young Catholics (OMK). This fact raises a great concern in this article, that most OMK are currently very busy with their work, study assignments, and social media, so that involvement in the activities of the parish becomes less effective and less targeted. The main issue in this article is to get a clear picture of how OMK is involved in the activities of the raid. This article wants to know the extent to which OMK is involved and involved in the pastoral work of the Church in the parishes of the Diocese of Ketapang. This article is qualitative research with descriptive analytical writing methods. The population used was Young Catholics in a number of parishes in the Diocese of Ketapang with a sample number of fifty-two active OMK. Instrument uses semistructured interviews to 12 OMK through WhatsApp social media. As a method of data collection, the authors disseminated questionnaires online to 40 OMK. The results showed that the involvement of OMK Keuskupan Ketapang in the activities of the church needs to be improved. Coaching to omk from the parish also needs to be designed and planned well. This study recommends the need for recollection, supply, retreat or similar activities that can grow and cultivate the faith of OMK. OMK is expected to be increasingly aware of self-identity as a young Catholic in the midst of the development of the times.